Canaries in the mines: children, risk, non-therapeutic research, and justice. Issue 2 (13th April 2004) - Spriggs, M
Abstract : The Kennedy Krieger lead paint study received a lot of attention after a US Court of Appeals ruled that a parent cannot consent to the participation of a child in non-therapeutic research. The ruling has raised fears that, if it goes unchallenged, valuable research might not proceed and ultimately all children would be harmed. The author discusses significant aspects of the study that have been neglected, and argues that the study was unethical because it involved injustice and its design meant that the study lacked importance and value. Issues of benefit, risk, and consent are vital, but it is sometimes a mistake to consider these issues before settling questions about justice and the importance and value of a research project. The author concludes by offering a strategy for researchers and reviewers of research to appreciate, in a vivid way, the implications of research participation.